Gluon fusion contribution to W+W- + jet production - Melia, T; Melnikov, K; Roentsch, R; Schulze, M; Zanderighi, G (2012)
We describe the computation of the gg → W +W -g process that contributes to the production of two W-bosons and a jet at the CERN Large Hadron Collider (LHC). While formally of next-to-next-to-leading order (NNLO) in QCD, this process can be evaluated separately from the bulk of NNLO QCD corrections because it is finite and gauge-invariant. It is also enhanced by the large gluon flux and by selection cuts employed in the Higgs boson searches in the decay channel H → W +W -, as was first pointed out by Binoth et al. in the context of gg → W +W - production. For cuts employed by the ATLAS collaboration, we find that the gluon fusion contribution to pp → W +W -j enhances the background by about ten percent and can lead to moderate distortions of kinematic distributions which are instrumental for the ongoing Higgs boson searches at the LHC. We also release a public code to compute the NLO QCD corrections to this process, in the form of an add-on to the package MCFM. © 2012 SISSA.